A study on adolescents to assess the impact of pictorial and textual warnings on panels of smoked and smokeless tobacco products in Western Maharashtra, India - Anand Thakur; K M Shivakumar; Snehal Patil; K V Suresh; Vidya Kadashetti (Wolters Kluwer Medknow Publications, 2015)
Introduction: Various pictorial and textual warnings are depicted with a hope that they will deter the individuals from using tobacco and inform them regarding the risks of tobacco. Yet there is lack of information regarding the comprehension of these signs by the adolescents. Aims: The aim was to explore the perception of the adolescents regarding the pictorial and textual warnings on tobacco packs. Materials and Methods: A cross-sectional study was conducted among 500 adolescents of Satara district using simple random sampling technique. A specially designed questionnaire was administered to assess understanding, credibility and persuasiveness of the pictorial and textual warnings on panel of smoked and chewable tobacco. A model containing the pictorial and textual warnings on panel of smoked and smokeless tobacco products were shown to the study subjects. Chi-square test was used for intergroup comparisons based on gender and age of the participants. The statistical analysis of data were done using SPSS version 20.0 (SPSS Inc., Chicago, IL, USA). Results: Nearly one-third of the study participants had often noticed warnings on tobacco packs in the last month, had sometimes read or looked closely at the warnings on tobacco packs in the last month and had rarely talked with anyone about these warnings. About more than two-third of the study participants had found the warning related pictures as not easy to understand, not believable and that these images did not deter them from the likely use of tobacco, and it did not stop them from using tobacco. Conclusion: We can infer that the textual and pictorial warnings failed to have desired deterrent impact on the adolescent who tend to initiate or continue the tobacco use despite the warning.